Collecting the yogurt from broken pot - Mumbai Archive Project Team (Jio Institute, 2024)
When the pot is broken, the crowd goes in a frenzy to collect the dahi (curd or yogurt) and smear it on their faces and bodies, chanting in unison, "Ala re ala, Govinda ala" (Govinda has arrived).